Gravity waves in the thermosphere simulated by GAIA - Miyoshi, Yasunobu; Fujiwara, Hitoshi; Jin, Hidekatsu; Shinagawa, Hiroyuki (2017)
18th EISCAT symposium Session E3: Ionoshere/thermosphere/mesosphere May 27 (Sat), NIPR Auditorium conference object